1982
DOI: 10.1177/000992288202100204
|View full text |Cite
|
Sign up to set email alerts
|

Pyogenic Liver Abscesses in Children

Abstract: Five children with pyogenic liver abscess were admitted to Institute of Child Health, Kabul during the period 1978 to 1980. All patients were males, and their ages ranged from 4 to 10 years. The clinical picture was characterized by fever, upper abdominal pain, enlarged tender liver with raised right dome of the diaphragm. The abscesses were located in the right lobe of liver in all cases, and they were solitary in three cases. Staphylococcus aureus was the etiologic agent in four cases and Escherichia coli in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 20 publications
2
10
0
Order By: Relevance
“…Liver abscess A total of 120 cases of pyogenic nonanaerobic bacterial hepatic abscess in childhood were reported (3,26,48). The microorganisms commonly recovered include Staphylococcus aureus, E. coli, Enterococcus faecalis, Klebsiella spp., Enterobacter spp., Pseudomonas organisms, and salmonellae.…”
Section: Intra-abdominal Abscessmentioning
confidence: 99%
“…Liver abscess A total of 120 cases of pyogenic nonanaerobic bacterial hepatic abscess in childhood were reported (3,26,48). The microorganisms commonly recovered include Staphylococcus aureus, E. coli, Enterococcus faecalis, Klebsiella spp., Enterobacter spp., Pseudomonas organisms, and salmonellae.…”
Section: Intra-abdominal Abscessmentioning
confidence: 99%
“…The microbiological species most often associated with liver abscesses in pediatric patients include Staphylococcus aureus, Escherichia coli, Klebsiella species, Enterobacter species, and Pseudomonas species (1,2). Anaerobes rarely account for these infections.…”
mentioning
confidence: 99%
“…Treatment for these frequently polymicrobial liver abscesses must include early antimicrobial coverage in addition to surgical drainage and debridement (1,7). Cefoxitin alone will not adequately cover all anaerobes since about 35% of Clostridiuin species are reported to be cefoxitin resistant (6).…”
mentioning
confidence: 99%
“…Till date, most studies have shown Staphylococcus aureus as the commonest causative agent of PLA followed by Gram-negative organisms. 3,5,21,22 In our study, we encountered a higher prevalence of Gram-negative bacteria. This is in concordance with 3 other Taiwanese studies which reported the dominance of K. pneumonia followed by E Coli.…”
Section: Discussionmentioning
confidence: 61%